Preliminary Clinical Assessment of I.C.R.F. 159 in Acute Leukaemia and Lymphosarcoma. Issue 5647 (29th March 1969) - Hellmann, K.; Newton, K. A.; Whitmore, D. N.; Hanham, I. W. F.; Bond, Jane V.
Abstract : I.C.R.F. 159, a new antitumour agent, has been assessed in six patients with acute leukaemia and three with lymphosarcoma. In all but two there was a considerable fall in circulating primitive cells, and in one there was bone-marrow evidence of a partial remission. Severe toxic effects were seen in only one case; they consisted of alopecia and gastroenteritis. It is suggested that I.C.R.F. 159 is worth further examination in all forms of acute leukaemia and lymphosarcoma.